Peranan Orang Tua Dalam Mendewasakan Iman Keluarga Kristen - Riana Udurman Sihombing; Rahel Rati Sarungallo (Jurnal Teologi dan Pelayanan Kerusso, 2019)
God wants to involve Himself in every family, because family is a small institution but important. Family is a symbol of the relationship between Christ and the church. Family is the God's place to express His love through relationships in love each other, mutual respect and care among all family members. God in His wisdom has given humans the best model and way of maturing in faith, through the role of parents as God's representatives to guide children. Likewise in modern times almost all parents (husband and wife) work outside automatically when gathering with children only at night. Sometimes children are asleep or studying, and parents feel tired and need rest. Such conditions and situations cause no opportunity for parents to communicate, guide and pay attention to the development of children.